THE ROLE OF SOLVING PROBLEMS AND EXERCISES IN BIOLOGY IN THE ACTIVATION OF COGNITIVE ACTIVITY OF STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The use of innovative technologies, including personality-oriented, in the process of teaching biology allows us to form the concept of self-development of students as a person. In particular, when teaching biology, it is possible to achieve the activation of their cognitive activity with the help of mass exercises.